Algeria's Ghardaia violence may rise in the long term - Oxford Analytica (Expert Briefings, 2015)
The potential for violence in GhardaiaViolent clashes took place on July 8 in the oasis city of Ghardaia in the south of Algeria, between the region's two major communities, the Arabs and the Berbers. Clashes between the two groups have occurred sporadically since the 1970s. However, the most recent ones were the most violent so far: 23 people died and dozens were injured. The government deployed 8,000 troops in the city, but the escalating violence has raised concerns about the government's ability to resolve the conflict.More violence in Ghardaia would damage the government's reputation, undermining its ability to solve domestic crises.This would lead to a further loss of credibility at home and abroad.It could also cause concerns among oil investors, at a time when Algiers is looking to increase its hydrocarbons production.
Keywords: Conflits -- Mzab

Forging Military Identity in Culturally Pluralistic Societies - Belkamel, Yassine (Lexington Books, 2015)
Keywords: Conflits -- Mzab

الاتصال الاستراتيجي خلال أزمة بريان نموذج مجلس العزابة في ولاية غرداية دراسة وصفية تحليلية - فرصوص, طه يونس (جامعة الجزائر 3, 2015)
Keywords: Conflits -- Mzab

M'zab Valley: Neither Sectarian nor Ethnic - Toumi, Abdennour (The Arab Daily News, 2015)
M'zab Valley: Neither Sectarian nor Ethnic By Abdennour Toumi Algiers, Algeria -- The recurring quarrels between the Mozabite and Cha'amba communities are
Keywords: Conflits -- Mzab

La guerre contre les ibadites de la Libye jusqu'à Ghardaïa - Adghirni, Ahmed (Trabrat.info, 2015)
Keywords: Conflits -- Mzab